Fiber-optic observations capture wind wave evolution in Lake Ontario - Yang, Chu-Fang; Spica, Zack; Fujisaki-Manome, Ayumi; Miao, Yaolin (Communications Earth & Environment, 2026)
Storm-induced waves threaten ship traffic and offshore infrastructures, yet observing water surfaces remains challenging because of complex air-water interactions and limited spatial coverage. We used distributed acoustic sensing measurements from a telecom fiber-optic cable in Lake Ontario, one of the world’s largest lakes, to analyze wind-wave evolution at tens-of-meter scales along a 43-km-long array. By combining observations and modeling, we found that chaotic waves induced by local wind forcing and wave-wave interactions generate high-frequency microseisms (1–4 Hz), whereas frequency variations in low-frequency microseisms (0.2–1 Hz) are strongly controlled by wind speed and fetch evolution. We tracked changes in frequency and energy throughout the full life cycle of wind waves, from chaotic conditions to organized gravity waves formed under steady winds, followed by dissipation as fetch decreases. These results are particularly relevant for fetch-limited water bodies and highlight the potential of distributed acoustic sensing for real-time monitoring of wind waves, with implications for coastal hazards, ecosystem dynamics, and wave-energy development.